2019
DOI: 10.5713/ajas.18.0692
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameters of chicken breast meat affected by carcass scalding conditions

Abstract: Objective The influence of broiler carcass scalding conditions on chicken breast meat quality parameters was investigated. Methods Two hundred and seventy Cobb broiler chickens from 42 to 48 days old were slaughtered according to the standard industry practice and scalded in five temperature/time combinations—T 1 , 54°C/210 s; T 2 , 55°C/180 s; T 3 , 56°C/150 s; T 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In contrast to this result, Sánchez del Pulgar et al [23] reported that sous vide pork cheeks cooked at 60 • C had a higher L* compared to those cooked at 80 • C. The authors concluded that samples cooked at lower temperatures preserved more water during cooking which might be released to the surface during the slicing process before color measurement. On the other hand, the chicken breast color can be classified into pale (L* > 53), dark (L* < 46), and normal (46 < L* < 53) based on the L* value [33]. In our study, sous vide chicken breast fillets in all combinations of temperature and time showed a pale appearance.…”
Section: Colormentioning
confidence: 50%
See 1 more Smart Citation
“…In contrast to this result, Sánchez del Pulgar et al [23] reported that sous vide pork cheeks cooked at 60 • C had a higher L* compared to those cooked at 80 • C. The authors concluded that samples cooked at lower temperatures preserved more water during cooking which might be released to the surface during the slicing process before color measurement. On the other hand, the chicken breast color can be classified into pale (L* > 53), dark (L* < 46), and normal (46 < L* < 53) based on the L* value [33]. In our study, sous vide chicken breast fillets in all combinations of temperature and time showed a pale appearance.…”
Section: Colormentioning
confidence: 50%
“…The color of meat samples before and after cooking was measured on the external surface of each fillet with a colorimeter (CR-400, Konica Minolta, Osaka, Japan) equipped with a standard illuminant D65 and 10 • observer angle [33]. The results are reported as L* (lightness), a* (redness/greenness), and b* (yellowness/blueness).…”
Section: Colormentioning
confidence: 99%
“…The association between the secondary proteins, amide I, amide II, and alpha helix, and high protein in HRFI could be explained by insulin resistance control when intramuscular lipids have accumulated as discussed earlier regarding the lower protein content of LRFI KR chickens ( Table 3 ). The high content of alpha helix in the HRFI KR chickens could be explained by the work of da Silva-Buzanello et al [ 36 ]. They reported that a high scalding temperature during the chicken slaughtering process could make conformational changes in protein by decreasing the alpha helix and increasing the beta sheet contents and the proportions of beta turn in the breast meat which contains the highest levels of polyunsaturated fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…Color of the skinless breast fillets was measured at 3 different locations (cranial, medial and caudal) using Minolta CR-400 with Spectra QC-400 software (Folio Instruments, Kitchener, ON, Canada) to identify possibly overscalded samples, following the CIE L*a*b* system, in which L* represents lightness, a* represents redness, and b* represents yellowness. Samples showing L* values equal or greater than 59 were removed from the WS assessment (Sirri et al, 2011;da Silva-Buzanello et al, 2019).…”
Section: Processing Measurementsmentioning
confidence: 99%